Comparative Analysis Of Banking Sector Financial Performance Before And During The Covid-19 Pandemic - Kholilah Kholilah; Anggra Saputra (Jurnal Akuntansi Terapan dan Bisnis, 2023)
This study aims to determine differences in financial performance before and during the covid-19 pandemic. The variables used to measure banking performance are Liquidity Ratio proxied by LDR/FDR, Profitability Ratio proxied by BOPO, ROA and NIM/NOM, and Solvency Ratio proxied by CAR. This research is quantitative research with a comparative approach. The data used is secondary data of quarterly banking financial statements obtained from the IDX official website. The population of this study is all banks listed on the IDX, the sample selection is done using purposive sampling technique, the number of samples in this study is 25 conventional banks and 2 Islamic banks. The data analysis method used is a different test with paired sample t-test and the Wilcoxon sign test. The results of this study indicate that there are differences in banking performance measured by the ratio of LDR/FDR and BOPO, and there is no difference in banking performance measured by ROA, NIM/NOM, and CAR.